Helping patients in Uganda overcome weight gain and obesity using motivational interviewing - James Docherty; Johanna Rochester (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2014)
Obesity is one of the fastest growing health problems in Uganda and across the world and its rising prevalence is placing additional strain on medical resources. At its simplest level obesity is a consequence of unhealthy lifestyles. Preventing its spread in Uganda will rest on the ability of society to motivate individuals to make positive healthy choices in their daily lives and many of the same techniques may be applicable to the situation in South Sudan.